Minutes of 21st technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 21st Technical and Progress Monitoring (TPM) meeting (session II) of BRACU new campus, held on 30th September, 2019.